Do ultra-poor graduation programs build resilience against droughts? Evidence from rural Ethiopia - Hirvonen, Kalle; Gilligan, Daniel O.; Leight, Jessica; Tambet, Heleene; Villa, Victor (International Food Policy Research Institute, 2023)
We study the role of a multifaceted ultra-poor graduation program in protecting household wellbeing and women’s welfare from the effects of localized droughts in Ethiopia. We use data from a large experimental trial of an integrated livelihood and nutrition intervention that supplemented the consumption support provided by Ethiopia’s Productive Safety Net Program (PSNP), conducted within a sample in which all households were beneficiaries of the PSNP. We match three rounds of household survey data to detailed satellite weather data to identify community-level exposure to droughts. We then exploit random assignment to the graduation program to evaluate whether exposed households show heterogeneous effects of drought on household food security and livestock holdings, women’s diets and nutritional status, and prevalence of intimate partner violence (IPV). We find that droughts have substantial negative effects on these outcomes, but the intervention serves to consistently moderate these effects, and for some outcomes (particularly diets and nutrition and IPV), the intervention fully protects households from any adverse drought affects. A further analysis exploits variation across treatment arms that received different program elements and suggests that the primary mechanism is enhanced household savings.